Conductive Thermoplastic Starch (TPS) Composite Filled with Waste Iron Filings - Danilo Battistelli; Diana P. Ferreira; Sofia Costa; Carlo Santulli; Raul Fangueiro (Emerging Science Journal, 2020)
A thermoplastic starch (TPS) was produced, starting with potato starch, glycerol and acetic acid, to shape it in films of thickness around 100 microns. To TPS iron waste filing particles, in the amount of 12% the weight of starch, were introduced in different modalities: as received, reduced in size by the use of a mortar, after treatment with hydrochloric acid, and after treatment and removal of hydrochloric acid. Morphological studies were carried out by optical and scanning electron microscopy and illustrated that the dispersion of iron filings was not optimal, though some improvement was observed by a reduced dimension of the particles. Tensile tests indicated the considerable improvement of stiffness offered by the insertion of iron particles to TPS, although the ultimate strain was reduced to less than 10%. Thermal characterization using thermogravimetry allowed revealing the three typical peaks for potato starch degradation, with only a slight decrease due to iron introduction. EDS allowed evaluating the presence of impurities in the iron filings and evidenced that the presence of iron was more effective on the surface than in the rest of the film. As a final consideration, An improvement in electrical conductivity by over an order of magnitude was obtained by the TPS+Fe+HCl film with respect to pure TPS.